Chirality of Hypervalent Chalcogenuranes - Drabowicz, Jozef; Chrzanowski, Jacek; Krasowska, Dorota; Zajac, Adrian (Current Organic Chemistry, 2016)
This review presents synthetic procedures applied to the preparation of chiral (mainly optically active) hypervalent chalcogenuranes. The stereoisomerization mechanisms of hypervalent derivatives of sulfur, selenium and tellurium and their selected interconversions are also presented.
Keywords: tellurane